ANALISIS FAKTOR PREDISPOSISI YANG BERHUBUNGAN DENGAN PERILAKU IBU DALAM PEMBERIAN IMMUNISASI HEPATITIS B0 PADA BAYI DI PUSKESMAS PEMBINA KOTA PALEMBANG - Retnaningsih, Ekowati; Rusmiati, Rini (Publikasi Penelitian Terapan dan Kebijakan, 2010)
Hepatitis B is one of all diseases becoming public health problem in the world. In Indonesia, prevalence of hepatitis B is 5-10%. It is increases in South Sumatera. The aims of study were to know relation between predisposing factor with immunization hepatitis B practice. Research design use the cross sectional design and total samples were 101 respondents. The result of the research were: 1) There was relation between the education, occupation, knowledge with the practice of baby immunization hepatitis B. 2) Mothers with height education have odd 2,88 times compare low education; Mothers do not have job have odd 4,99 times compare have job; Mothers with height knowledge have odd 2,87 times compare low knowledge, to give hepatitis B0 for her baby.